Fabrication of zinc oxide nanostructures on zinc foil by wet oxidation method - Pelicano, Christian Mark O.
Zinc oxide (ZnO) is a key multifunctional semiconductor material which is important for munerous applications such as light emitting diodes (LED), photodetectors, gas sensors, solar cells, and photocatalysis. ZnO can be grown by a variety of techniques such as hydrothermal method, chemical vapor deposition, and magnetron sputtering, among others. However, several factors limit the applicability of some of these methods, particularly in producing nanostructured ZnO. Some of these factors include the use of toxic chemical reagents, extremely high temperature, and expensive sophisticated equipment. Thus, it is necessary to develop a simple, economical and low temperature method for the preparation of Zno nanostructures, which can be easily up-scaled for industrial application. The integration of the method with flexible substrates such as organic polymers for future portable electronics is possible since the process takes place at a low temperatme. In this study, the growth of ZnO nanostructures at low temperatures by wet oxidation in water is presented. Based on the existing literature, no current studies have investigated the influence of different parameters, such as substrate etching, growth time and temperature, solution pH and addition of Zn ions on the morphology of ZnO nanostructures produced using wet oxidation in water. Hemispherical stmctmes of ZnO nanowires, nanorods, nanotubes and nanoflowers were obtained on etched Zn foil at increasing oxidation times at 90°C. These ZnO nanostructures exhibited good crystallinity and optical properties as demonstrated by X-ray diffraction analysis and photoluminescence observations. Wet oxidation of pristine Zn substrate produced relatively aligned nanorods with the structure becoming coarser after longer oxidation time. Herein, the growth of one dimensional Zno nanostructures can be attributed to the wurtzite crystal structure of ZnO. After wet oxidation of etched Zn foil for 4 h, a thin layer of film with minute needle-like structures was formed at room temperature while hemispherical strurctures of ZnO nanorods were formed at elevated temperatures. However, increasing the oxidation temperature to the boiling point of water resulted to coarse ZnO nanorods. These results suggest that the optimum temperature for wet oxidation in water is 90°C for the growth of even and unifirm Zno nanostructures. At acidic condition, only large grooves were observed on Zn substrate after wet oxidation for 4h at 90°C. On the other hand, flower-like structures of coarse nanorods and nanotubes were produced in basic conditions. In situ monitoring of solution redox potentials combined with thermodynamic calculations was performed to further explain the growth of Zno nanostructures at different growth temperatures and solution pH. Clusters of ZnO nallosheets were visibly grown on top of hexagonal flat-topped nanorods in the presence of 0.05 M ZnCI2. Addition of higher ZnCl2 concentration resulted to layered plate-like structures of simonkolleite compound (Zn5(OH)8Cl2H2O). Moreover, the method was successfully applied on vacuum deposited Zn thin film on glass/ITO substrates to produce Zno nanorods, nanotubes and lotus-like structures at increasing oxidation times. A hybrid organic-inorganic solar cell following an inverted bulk heterojunction configuration was then fabricated based on the lotus-like structures. The solar cell achieved a power conversion efficiency of up to 1.18% showing tile applicability of wet oxidized ZnO for photovoltaic application